Reading bots: The implication of deep learning on guided reading - Huang, Baorong; Dou, Juhua; Zhao, Hai (Frontiers in Psychology, 2023)
This study introduces the applications of deep-learning technologies in automatically generating guidance for independent reading. The study explores and demonstrates how to incorporate the latest advances in deep-learning-based natural language processing technologies in the three reading stages, namely, the pre-reading stage, the while-reading stage, and the post-reading stage. As a result, the novel design and implementation of a prototype system based on deep learning technologies are presented. This system includes connections to prior knowledge with knowledge graph and summary-based question generation, the breakdown of complex sentences with text simplification, and the auto-grading of readers' writing regarding their comprehension of the reading materials. Finally, the study reveals the challenges and limitations of deep learning technologies for future improvement.